GelMA–GelDopa–Sr double-network hydrogel promotes skin regeneration by enhancing angiogenesis and macrophage polarization - Su, Yuxuan; Zhao, Fang; Liu, Shuang; Dong, Zheqin; Liu, Dongxu (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionChronic skin defects typically exhibit persistent inflammation, damaged cell regeneration, and insufficient vascularization, all of which severely impede the healing process. Traditional skin dressings merely serve to cover the wound and do not actively promote wound healing. They lack anti-inflammatory capabilities and only minimally regulate immune cells, and their poor biocompatibility can lead to foreign body reactions. Some traditional dressings adhere to the defect area, and during dressing changes, they may cause secondary trauma, resulting in pain and tearing of new tissue. Therefore, it is of great significance to develop a functional dressing that can simultaneously regulate inflammatory responses, promote angiogenesis, and accelerate tissue regeneration.MethodsIn this study, gel methacrylamide (GelMA), gel dopamine (GelDopa) were combined with strontium ions (Sr2+) to create a multifunctional dual-network composite hydrogel, GelMA-GelDopa-Sr hydrogel. CCK-8 and live/dead cell staining assays were used to detect fibroblast proliferation. Scratch and transwell assays were used to assess cell migration. Vascular networks were evaluated by tube formation experiments.ResultsThis dual-network design provided several functional advantages: the photopolymerization properties of GelMA enabled rapid and controllable gelation; the catecholamine derived from GelDopa imparted antioxidant capabilities, thereby reducing oxidative stress; and Sr2+ promoted angiogenesis. In vivo evaluations demonstrated that the fabricated GelMA-GelDopa-Sr hydrogel significantly promoted fibroblast proliferation, accelerated cell migration, and promoted the formation of stable vascular networks. In a full-thickness skin defect rat model, the GelMA-GelDopa-Sr hydrogel significantly upregulated levels of CD31 and CD163, indicating that the hydrogel enhanced angiogenesis and regulated the immune environment, which accelerated wound healing.DiscussionThe results show that the GelMA-GelDopa-Sr dual-network composite hydrogel exerts antioxidant, angiogenic promotion and immune regulation effects through a synergistic mechanism, which overcomes the challenges of inflammation and insufficient vascularization during skin tissue regeneration and significantly accelerates the regeneration of skin tissues. This research offers new ideas and experimental basis for the design and application of multifunctional hydrogels in the repair of chronic wounds.